Validation of the Korean version of the oral health impact profile among the Korean elderly - Bae K-H, Kim H-D, Jung S-H, Park D-Y, Kim J-B, Paik D-I, Chung S-C. (Blackwell Synergy, 2007)
This study aimed to validate a Korean version of the oral health impact profile (OHIP) and to develop a short-form of OHIP for the Korean elderly.